EVALUASI KINERJA DINAS PENDAPATAN DAERAH KOTA DENPASAR BERBASIS BALANCED SCORECARD - Limbu, Wanda Pramudani; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2016)
This study aims to determine the performance of the local authorities in Denpasar Revenue Service. Performance is measured through four perspectives: financial, customer, internal business process, and learning and growth perspective, which is part of the Balanced Scorecard method. The method used in this research is descriptive method by analyzing data from four perspectives: financial perspective, as measured by the method of Value for Money, internal business process perspective is measured by the ratio Service Cycle Efficiency (SCE), the customer perspective with customer satisfaction index and learning and growth with employee satisfaction index. Results from this study indicate that the performance viewed from financial perspective can be said to be economical, efficient and effective. Performanced from the customers perspective is good which is signed by satisfied costomers; Internal business also shows an efficient process; and from the perspective of learning and growth, the performance also shows satisfied employees.
Keywords: Balanced Scorecard, Perspectives, Performance